Understanding why people do or do not engage in activities following total joint replacement: a longitudinal qualitative study. Issue 6 (June 2015) - Webster, F.; Perruccio, A.V.; Jenkinson, R.; Jaglal, S.; Schemitsch, E.; Waddell, J.P.; Venkataramanan, V.; Bytautas, J.; Davis, A.M.
Summary: Objective: Numerous studies report large and significant improvements in basic mobility and activities of daily living following total hip or knee replacement (TJR). Nevertheless, quantitative research has shown minimal increase in participation in activities that benefit overall health. This study explored why people do or do not engage in activities following hip or knee TJR. Method: This was a longitudinal qualitative study. Sampling was guided by constructivist grounded theory and data collected using open-ended, semi-structured interviews. Participants were recruited using maximum variation sampling based on age, sex and joint replaced (hip or knee). Data were analysed using a constant comparative approach and coded for thematic patterns and relationships from which overarching themes were constructed. Results: Twenty-nine patients participated in interviews prior to, and 8 and 18 months post following TJR. A high degree of variability with regard to participants' return to activities was found and five emergent themes were identified that accounted for this variability. These themes highlight the importance of issues beyond medical factors alone, such as socio-cultural factors that partially determine participants' participation in activity following TJR. Conclusion: Findings suggest that multi-faceted experiences impact participation in activity following TJR. These experiences include changes in identity and lifestyle that preclude a 'return to normal'. There is an urgent need for supports to increase people's activity post-TJR in order to facilitate enhancement of post-surgery levels of engagement. Approaches that take into consideration more personalized interventions may be critical to promoting healthy aging in people with TJR.